Research on the High Performance Flux-weakening Control Strategy of Permanent Magnetic Synchronous Generator for Wind Turbine - ZHANG Zhaoyang; XU Junfeng; LIU Xiong (Kongzhi Yu Xinxi Jishu)
It analyzes the anti-windup strategy of synchronous current PI regulator for IPMSG and presents a method of adaptive fluxweakening control. This method, using the difference between reference voltage and actual voltage, can increase output torque of generator. Experimental results prove the validity of this method.